1973
DOI: 10.1159/000136377
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of the Hexobarbital Enantiomers with Rat Liver Microsomes

Abstract: There is a stereoselective difference in the interaction of the hexobarbital enantiomers with rat liver microsomes. The metabolism of the hexobarbital isomers was elevated in microsomes isolated from rats pretreated with phenobarbital and the (+)-isomer metabolized to a greater degree in control and phenobarbital-induced preparations. (+)-Hexobarbital was observed to be more effective than the (–)-isomer in the stimulation of endogenous NADPH oxidation and inhibition of ethylmorphine N-demethylation. In bindin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1975
1975
1991
1991

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 4 publications
(7 reference statements)
0
1
0
Order By: Relevance
“…The metabolism of racemic hexobarbitone has been studied extensively in man (Breimer & Van Rossum, 1973;Breimer et al, 1975a, b;Zilly et al, 1975Zilly et al, , 1978 and animals (Bush & Weller, 1974;Degwitz et al, 1969;Feller & Lubawy, 1973;Furner et al, 1969;McCarthy & Stitzel, 1971;Van der Graaf et al, 1983) and has been shown to be dependent upon the cytochrome P-450 mixed function oxidase system. The 3-hydroxylation of hexobarbitone has been shown to cosegregate with the mephenytoin polymorphism (Knodel et al, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…The metabolism of racemic hexobarbitone has been studied extensively in man (Breimer & Van Rossum, 1973;Breimer et al, 1975a, b;Zilly et al, 1975Zilly et al, , 1978 and animals (Bush & Weller, 1974;Degwitz et al, 1969;Feller & Lubawy, 1973;Furner et al, 1969;McCarthy & Stitzel, 1971;Van der Graaf et al, 1983) and has been shown to be dependent upon the cytochrome P-450 mixed function oxidase system. The 3-hydroxylation of hexobarbitone has been shown to cosegregate with the mephenytoin polymorphism (Knodel et al, 1988).…”
Section: Discussionmentioning
confidence: 99%